Racial Discrimination in South Korea: Korean Academics Offer Proposals for a Solution, but What if the Solution is Inherent to the Korean Constitution? - Peter D. Klein (American Scientific Research Journal for Engineering, Technology, and Sciences, 2022)
Korea has been a homogenous culture for over five thousand years. Although it has faced incursions and occupations, it has always repelled those advances and maintained racial, linguistic, and cultural purity with surprising resoluteness. However, Korea’s modernization and economic expansion required alliances and policies that introduced multicultural forces into its once pure society, creating sizable racial minorities for the first time in history. The government’s shift from authoritarian rule to liberal democracy has given voice to these minorities. These groups are demanding admittance to an exclusive society, along with equal and humane treatment. The people and government of Korea are now faced with the dilemma of dispensing with the exclusive dominance of their age-old, ‘pure’ culture to accommodate different ethnicities and practices. This paper will discuss the problems and potential solutions, including one that may already exist untapped in the Korean constitution.